2021
DOI: 10.3389/fcvm.2021.662914
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Calcium Homeostasis and Release Events Under Atrial Fibrillation and Its Risk Factors: A Meta-Analysis

Abstract: Background: Atrial fibrillation (AF) is associated with calcium (Ca2+) handling remodeling and increased spontaneous calcium release events (SCaEs). Nevertheless, its exact mechanism remains unclear, resulting in suboptimal primary and secondary preventative strategies.Methods: We searched the PubMed database for studies that investigated the relationship between SCaEs and AF and/or its risk factors. Meta-analysis was used to examine the Ca2+ mechanisms involved in the primary and secondary AF preventative gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…ACE2 is also involved in the regulation of the cardiac action potential. Ang(1–7) modulates Ca 2+ homeostasis and cellular electrophysiology in atrial tissue and pulmonary veins ( 46 , 47 ). Experimental animal studies have demonstrated an increased expression of ACE2 receptor following treatment with ACE inhibitors and angiotensin receptor blockers ( 48 ).…”
Section: The Outline Of Af Pathophysiologymentioning
confidence: 99%
“…ACE2 is also involved in the regulation of the cardiac action potential. Ang(1–7) modulates Ca 2+ homeostasis and cellular electrophysiology in atrial tissue and pulmonary veins ( 46 , 47 ). Experimental animal studies have demonstrated an increased expression of ACE2 receptor following treatment with ACE inhibitors and angiotensin receptor blockers ( 48 ).…”
Section: The Outline Of Af Pathophysiologymentioning
confidence: 99%
“…As a nonselective monovalent cation channel, TRPM4 upregulation and activation enhance sodium entry, which leads to depolarization of the membrane potential. The membrane potential is critical in regulating calcium influx; calcium dysregulation is known to play an essential role in predisposing to tachy-arrhythmias and sudden cardiac death [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TGF-β1 pathway initiates inflammation and oxidative stress signaling and is important in ECM regulation and atrial fibrotic remodeling [ 11 ]. TSP-1 also interacts with cardiac matrix metalloproteinases (MMPs), collagen I and ionized calcium (Ca 2+ ) [ 12 ], which are thought to be critical in atrial ECM metabolism [ 13 , 14 ]. We summarized a figure of TSP-1 binding partners possibly related with atrial ECM remodeling (Fig.…”
Section: Introductionmentioning
confidence: 99%